Progress in Treatment of Post Inflammatory Pulmonary Fibrosis Induced by SARS-CoV-2 Infection - HUANG Lihui, SHU Juan, TAO Huihui, BAO Hairong (Zhongguo quanke yixue, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a major public health emergency in the world, which poses a major threat to the global health system. After rehabilitation from SARS-CoV-2 infection, some patients may experience multiple respiratory symptoms for a long time, which is called the acute sequelae of SARS-CoV-2 infection. Post-COVID-19 pulmonary fibrosis (PCPF) as one of them, can affect the respiratory function and quality of life of patients to varying degrees. Regarding the treatment of PCPF is a hot topic in current research, and this article provides a review of treatment methods for PCPF, aiming to improve the prognosis of PCPF patients.